Mutu Bakteriologis Pindang Tongkol (Euthynnus affinis) yang Berasal dari Beberapa Pasar di Yogyakarta - Ekawati Purwijantiningsih; Exsyupransia Mursyanti (Universitas Atma Jaya Yogyakarta, 2006)
Food poisoning cases need to be examinated intensively. There have been five poisoning cases reported between 2003-2004 in Sleman area. Three of them were caused by contaminated tuna fish. The objective of this research was to determine bacteriological quality of salted tuna fish from several markets in Yogyakarta. Salted tuna fish sample were collected from five markets, namely Beringharjo, Condongcatur, Demangan, Kranggan and Sentul. In each market, four vendors were selected. Bacteriological test were done including total microbe cells utilizing PCA medium, Coliform test utilizing VRBA medium. Identification and isolation of Vibrio parahaemolyticus use pre-enrichment selective medium of Alkaline Petone Water and selective Chromogenic medium agar for Vibrio. Salmonella test utilizing Chromogenic agar continued by utilizing TSI and LIA medium. The result showed that bacteriological quality of salted tuna fish from markets in Yogyakarta did not fulfill the requirements based on SNI 01-2717-1992. It was shown that total microbial count were high, i.e. 2.4 x 105 – 5.27 x 107 CFU/ g. Coliform count ranged from < 2.5 x 101 - > 6.5 x 106 CFU/g. From 20 samples that were brought to analyzed, 60% was positively presumed contaminated by V. parahaemolyticus and 50% was positively presumed contaminated by Salmonella.